Non-Financial Enterprise Financialization, Product Market Competition, and Total Factor Productivity of Enterprises - Long Miao; Yue Zhuo; Haojun Wang; Bei Lyu (SAGE Open, 2022)
At present, two big challenges have struck China’s economic development: economic containment “from the real to the virtual” and accomplishment in the goal of high-quality economic development. Taking China’s A-share public manufacturing enterprises from 2007 to 2020 as samples, this paper empirically analyzes the relationships among product market competition, non-financial enterprise financialization, and total factor productivity of enterprises. It is found that non-financial enterprise financialization significantly lowers down the total factor productivity of enterprises, that is, the total factor productivity of enterprises will drop by 1.7% as the non-financial enterprise financialization rises by 1 SD every time. After external regulation effects of product market competition are further taken into account, the furious product market competition, on the whole, mitigates the negative influences of non-financial enterprise financialization on total factor productivity of enterprises by strengthening the role of non-financial enterprise financialization as a “reservoir” and abating the “crowding-out” effect. Therefore, competition promotion policies combined with funds moving “from the virtual to the real” could more effectively elevate the enterprise productivity.